DIPLOMATIC RELATIONS BETWEEN BRITAIN AND KENYA - Githii , John (European Journal of Historical Research, 2021)
Purpose: Kenya's foreign policy has largely rested with the presidency as has been shown by the analysis of the Uhuru Kenyatta Regimes. The general objective of the study was to examine diplomatic relations between Britain and Kenya. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study concludes that Kenya and Britain established diplomatic relations in pursuit of their respective interests in line with the Realist tradition. The diplomatic relations led to the two countries signing treaties and conventions as provided for in Article 2(6) of the constitution. Both countries keep defining and redefining their national interest. Public officers have benefited from training in Britain including doctors who have acquired specialized medical training and skills that have benefited Kenya. Military relations between these two countries have played a role in determining economic, trade, diplomatic and political relations. It was also revealed that Britain has maintained its economic interests since the colonial period to date. Recommendations: The study recommends that there is need for Kenya to strengthen its relations with Britain especially in the areas of economic development as Britain is one of the key investors and trading partners of Kenya. This would be achieved by the country's Foreign Ministry negotiating deals that will benefit the country. Kenya should also ensure that the British military base in Laikipia trains Kenyan soldiers on the military tactics applied by Britain to ensure they improve the security within the Country and across the borders. This would ensure they minimize the terrorist threats that the country faces. The political relations should be used as a bench mark to ensure that Kenya has the best governance structure that will promote ethical leadership, eliminate corruption and compel the leaders to be accountable to the citizenry. This will ensure that resources are channeled and used in the right sectors for development.